Spatio-temporal assessment of regional scale evolution and distribution of glacial lakes in Himalaya - Mohanty, Litan; Maiti, Sabyasachi; Dixit, Ankur (Frontiers in Earth Science, 2023)
Glacial lakes are a potential threat to the livelihoods and precious infrastructures in the Himalayan region. The expansion of these lakes under the influence of global warming further poses a grievous risk of natural disasters in the form of glacial lake outburst flood (GLOF) that necessitates regular monitoring to reduce and mitigate its implications. This research focuses on the regional scale distribution and evolution of glacial lakes in the Himalayan mountain range with their causes. We used Landsat thematic mapper (TM) and operational land imager (OLI) images, Google Earth imageries, Shuttle radar topographic mission (SRTM) Digital Elevation Model, and Aphrodite climatic data to study lake evolution and its controlling parameters. A total of the 5,409 glacial lakes was taken for the size expansion analysis, which excludes supraglacial lakes. An expansion rate of 2.98%/yr and 1.01%/yr in glacial lakes number and size was found from 1990 to 2020, respectively. The glacial lakes are distributed mainly in Langtang, Bhutan, Sikkim and Everest region; while, new lakes are forming at higher elevations continuously. The highest lake size expansion was noted in 2015–2020 (36.51%) followed by 2000–2010 (21.72%) and 2010–2015 (10.65%), while 1990–2000 (3.36%) showed a lowest expansion rate. The highest expansion rate was noticed near an elevation band of 5000–5500 m. Moreover, lakes in the central and eastern Himalaya are highly decrease by climatic change, i.e., increase in temperature a decrease precipitation. The feature selection algorithm was used to identify the importance of various controlling parameters, which showed temperature change rate, glacier fed lake, glacier snout steepness, proximal distance, glacier calving frontal width, precipitation change rate and lake type gave higher weightage towards lake size change.